How to deal with the challenges of linking a large number of individual national models: the case of the AGMEMOD Partnership - Petra Salamon; Fred́eŕic Chantreuil; Trevor Donnellan; Emil Erjavec; Roberto Esposti; Kevin Hanrahan; Myrna van Leeuwen; Foppe Bouma; Wietse Dol; Guna Salputra (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
The AGMEMOD Partnership seeks to capture the inherent existing heterogeneity of agricultural systems by linking together individual EU Member State models, an aggregated EU model and several accession countries into one single model, while still maintaining analytical consistency. Although this approach facilitates the comparison of the impact of a policy change across different Member States, it generates challenges in practical implementation, ranging from significant communication and administration requirements, to aggregation and consistency issues. This contribution provides insights into the different challenges posed to the scientists and discusses the key issues for maintenance and further development of such a complex system. Specific attention is paid to technical devices and tools as well as to the design of institutional settings to achieve consistency.
Keywords: 330; EU-Agrarpolitik; Wirkungsanalyse; Forschungskooperation; Wirtschaftsmodell; EU-Staaten